Green catalytic synthesis method of succinic anhydride

Through the supported nickel carbide coated nickel nanocomposite catalyst, the problems of complex preparation and poor stability of existing catalysts in the production of succinic anhydride are solved, and efficient and low-cost succinic anhydride production are achieved, which is suitable for industrial applications.

CN119161313AActive Publication Date: 2024-12-20TAN KAH KEE INNOVATION LAB +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411370992.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-20
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

In the production process of succinic anhydride, existing catalysts have problems such as complex preparation, high prices, harsh temperature and pressure, and poor catalyst reuse stability, which is difficult to meet the needs of industrial applications.

Method used

Use the supported nickel carbide coated nickel nanocomposite as a catalyst to prepare succinic anhydride by hydrogen catalyzing malic anhydride, and use the nickel carbide shell to protect the nickel nanoparticles, achieving high reactivity and high selectivity, and the catalyst is easy to separate and use multiple times. .

Benefits of technology

High reaction activity and high selectivity are achieved under mild reaction conditions, reducing the cost of the catalyst, the catalyst can be reused multiple times and has high stability, making it suitable for industrial scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides a green catalytic synthesis method of butanedioic anhydride, which comprises the following steps: catalyzing maleic anhydride to prepare butanedioic anhydride by taking a supported nickel carbide coated nickel nano composite material as a catalyst and hydrogen as a hydrogen source, the supported nickel carbide coated nickel nano composite material is composed of an activated carbon carrier, an active metal nickel core and a nickel carbide shell coated on the surface of the active metal nickel core. Compared with the prior art, the specific nickel-based catalyst is adopted, the catalyst realizes high reaction activity of maleic anhydride hydrogenation and high selectivity of a single product succinic anhydride under mild reaction conditions, a nickel carbide shell can protect internal nickel nanoparticles from being poisoned, repeated application can be realized, the cost of the catalyst is reduced, and the catalyst is suitable for industrial production. Meanwhile, after reaction, the catalyst is easily separated from hydrogenation mother liquor, can be used for multiple times without inactivation, and has better stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of organic chemical synthesis, and more specifically to a green catalytic synthesis method of succinic anhydride. Background Art

[0002] Succinic anhydride (SA), also known as succinic anhydride, is an extremely important organic synthesis intermediate. It is currently widely used in the synthesis of food, medicine, pesticides, dyes, esters and resins. Among them, the synthetic resin industry is used to manufacture alkyd resins and ion exchange resins, and the pesticide industry is used to create plant growth regulators. A more important application is that the hydrolysis product of succinic anhydride, succinic acid, reacts with 1,4-butanediol to undergo an esterification reaction to form a biodegradable plastic-polybutylene succinate (PBS). As the problem of white pollution becomes increasingly serious, the country has also issued many policies to strengthen the control of the plastics industry. The price of PBS is lower than that of other degradable plastics, and it has good heat resistance and excellent mechanical properties, and has broad market prospects. The rapid development of the PBS industry will inevitably greatly increase the market demand for succinic anhydride, but the current production capacity of succinic anhydride in my country is very limited and cannot meet the future needs of PBS industrialization. Therefore, the production technology of succinic anhydride becomes particularly critical.

[0003] At present, the main methods for producing succinic anhydride are paraffin oxidation, biological fermentation and maleic anhydride hydrogenation. Maleic anhydride hydrogenation has the advantages of simple process, low energy consumption and good atom economy. Therefore, the development of highly active and highly selective catalysts to achieve maleic anhydride hydrogenation to produce succinic anhydride has great social significance and economic value.

[0004] Catalysts for the catalytic hydrogenation of maleic anhydride are mainly divided into two types, homogeneous catalysts and heterogeneous catalysts. Homogeneous catalysts such as Bai Zhanqi et al. (Study on the homogeneous coordination catalytic hydrogenation of maleic anhydride to produce succinic anhydride [J] Chemical Reaction Engineering and Technology, 1998, 14 (2): 185-189) developed ruthenium phosphine complex catalysts for maleic anhydride hydrogenation reaction. Under the optimal conditions of 100°C and 3 MPa, the maleic anhydride conversion rate was 98.4% after 4 h of reaction, and the selectivity of succinic anhydride was 100%. Although homogeneous catalysts show good catalytic effects, due to the use of precious metal Ru, which is dispersed in the solvent and the product during the reaction, it is difficult to separate and reuse after the reaction is completed, and the product is easily doped with the catalyst, resulting in reduced quality, so it cannot be used industrially.

[0005] Heterogeneous catalysts have the advantages of strong designability, clear structure, low price and easy separation from hydrogenation mother liquor, and have more industrial application prospects. US5952514 uses a catalyst formed by pressing Fe, Co, Ni, C, and Au powders for preparing succinic anhydride from maleic anhydride. The reaction is carried out on a fixed bed. Under the conditions of reaction temperature of 60~180℃ and pressure of 38 MPa, the maleic anhydride conversion rate is 99%, and the succinic anhydride selectivity is as high as 98%. The disadvantage is that the reaction pressure is too high, resulting in high equipment cost and potential safety hazards. CN03122336.2 discloses a catalyst with nickel as active component and aluminum oxide and silicon dioxide as carrier for catalytic hydrogenation of maleic anhydride to prepare succinic anhydride. The catalytic hydrogenation reaction is carried out under the conditions of solvent or solvent-free, reaction temperature of 120~180℃, and reaction pressure of 0.5 MPa~3 MPa. Due to the high reaction temperature, the product maleic anhydride undergoes polymerization reaction, resulting in excessive product chromaticity. CN101502802A discloses a nickel-based catalyst, which uses nickel as an active component, adds 1% to 7% of a promoter, and uses alumina, silicon dioxide or a composite of the two as a carrier. Maleic anhydride is hydrogenated in a fixed bed reactor under the conditions of 0.9 MPa to 10 MPa and 60°C to 180°C. The maleic anhydride conversion rate is as high as 99.98% or more, and the selectivity of succinic anhydride is greater than 98.85%, but the catalyst is easily poisoned and deactivated. Meyer et al. (Applied Catalysis A: General, 2009, 367(1): 122-129) used 10% Cu / SiO2 to catalyze the hydrogenation of maleic anhydride to produce succinic anhydride. Under the conditions of a reaction temperature of 220°C and a hydrogen pressure of 1 bar, the selectivity of the product succinic anhydride was as high as 98%. However, the researchers found that after the reaction was carried out at 170°C to 220°C for 200 min, the catalyst had different degrees of deactivation, with the maximum deactivation degree reaching more than 60%.

[0006] Although the above catalysts all show high conversion rate and selectivity in the reaction of hydrogenating maleic anhydride to prepare succinic anhydride, the catalysts used still have disadvantages such as complex preparation process and high price. In addition, the temperature and pressure conditions required for the catalytic reaction of the catalyst are relatively harsh, and the catalyst has poor stability in repeated use. Summary of the invention

[0007] In view of this, the object of the present invention is to provide a green catalytic synthesis method of succinic anhydride, which can prepare a nickel-based catalyst by a simple and efficient method. The catalyst achieves high reaction activity and high selectivity for a single product, succinic anhydride, in hydrogenation of maleic anhydride under relatively mild reaction conditions. After the reaction, the catalyst is easily separated from the hydrogenation mother liquor, can be used multiple times without deactivation, and has good stability.

[0008] The present invention provides a green catalytic synthesis method of succinic anhydride, comprising the following steps:

[0009] The supported nickel carbide coated nickel nanocomposite material is used as a catalyst and hydrogen is used as a hydrogen source to catalyze maleic anhydride to prepare succinic anhydride; the supported nickel carbide coated nickel nanocomposite material is composed of an activated carbon carrier, an active metal nickel core and a nickel carbide shell coated on the surface of the active metal nickel core.

[0010] Preferably, the process of catalyzing maleic anhydride to prepare succinic anhydride is specifically as follows:

[0011] The catalyst, maleic anhydride and solvent are added into a high-pressure reactor, and hydrogen is continuously introduced for hydrogenation reaction to obtain succinic anhydride.

[0012] Preferably, the mass ratio of the catalyst, maleic anhydride and solvent is (0.02-0.2):1:(5-50).

[0013] Preferably, the temperature of the hydrogenation reaction is 80°C to 120°C, the hydrogen pressure is 0.1 MPa to 5 MPa, and the time is 0.5 h to 12 h.

[0014] Preferably, the solvent is selected from one or more of methanol, ethanol, DMF, DMSO, toluene, n-hexane, acetone, tetrahydrofuran and 1,4-dioxane.

[0015] Preferably, the content of active metal nickel in the supported nickel carbide-coated nickel nanocomposite material is 1 wt% to 40 wt%.

[0016] Preferably, the specific surface area of ​​the activated carbon carrier is 800 m 2 / g~1500 m 2 / g, and the average pore size is 0.5 nm~5nm.

[0017] Preferably, the active metal nickel core has a face-centered cubic crystal structure.

[0018] Preferably, the preparation method of the supported nickel carbide-coated nickel nanocomposite material is specifically as follows:

[0019] The activated carbon and the nickel salt solution are mixed and dried, and then reduced with hydrogen to obtain activated carbon-supported nickel nanoparticles; the surface of the obtained activated carbon-supported nickel nanoparticles is then carbonized with a carbon-containing gas to obtain a supported nickel carbide-coated nickel nanocomposite material.

[0020] Preferably, the temperature of the hydrogen reduction is 350°C to 550°C, and the time is 1 h to 4 h;

[0021] The surface carbonization temperature is 150° C. to 300° C., and the time is 0.5 h to 5 h.

[0022] The present invention provides a green catalytic synthesis method of succinic anhydride, comprising the following steps: using a supported nickel carbide coated nickel nanocomposite material as a catalyst and hydrogen as a hydrogen source to catalyze maleic anhydride to prepare succinic anhydride; the supported nickel carbide coated nickel nanocomposite material is composed of an activated carbon carrier, an active metal nickel core, and a nickel carbide shell coated on the surface of the active metal nickel core. Compared with the prior art, the present invention adopts a specific nickel-based catalyst, which achieves high reaction activity of maleic anhydride hydrogenation and high selectivity of a single product, succinic anhydride, under milder reaction conditions, and the nickel carbide shell can protect the internal nickel nanoparticles from being poisoned, and can be used multiple times to reduce the catalyst cost. At the same time, after the reaction, the catalyst is easily separated from the hydrogenation mother liquor, can be used multiple times without deactivation, and has good stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 TEM and particle size distribution diagram of catalyst A;

[0024] Figure 2 XRD patterns of activated carbon, catalyst B and catalyst A, among which Ni@NiC x / C is catalyst A, Ni / C is catalyst B, and C is activated carbon;

[0025] Figure 3 The nitrogen adsorption and desorption isotherms of activated carbon, catalyst B and catalyst A are shown in Figure 2. x / C is catalyst A, Ni / C is catalyst B, and C is activated carbon;

[0026] Figure 4 TEM and particle size distribution diagram of catalyst H. DETAILED DESCRIPTION

[0027] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] The present invention provides a green catalytic synthesis method of succinic anhydride, comprising the following steps:

[0029] The supported nickel carbide coated nickel nanocomposite material is used as a catalyst and hydrogen is used as a hydrogen source to catalyze maleic anhydride to prepare succinic anhydride; the supported nickel carbide coated nickel nanocomposite material is composed of an activated carbon carrier, an active metal nickel core and a nickel carbide shell coated on the surface of the active metal nickel core.

[0030] The invention provides a method for preparing succinic anhydride by catalyzing maleic anhydride hydrogenation using a supported nickel carbide coated nickel nanocomposite material as a catalyst.

[0031] In the present invention, the supported nickel carbide-coated nickel nanocomposite material consists of an activated carbon carrier, an active metal nickel core and a nickel carbide shell coated on the surface of the active metal nickel core; the particle size of the active metal nickel core is 5 nm~15 nm, and the thickness of the nickel carbide shell is 0.1 nm~10 nm.

[0032] In the present invention, the content of active metal nickel in the supported nickel carbide-coated nickel nanocomposite material is preferably 1 wt% to 40 wt%, more preferably 10 wt% to 40 wt%.

[0033] In the present invention, the specific surface area of ​​the activated carbon carrier is preferably 800 m 2 / g~1500 m 2 / g, and the average pore size is preferably 0.5 nm~5 nm.

[0034] In the present invention, the active metal nickel core is preferably a face-centered cubic crystal structure.

[0035] In the present invention, the preparation method of the supported nickel carbide-coated nickel nanocomposite material is preferably as follows:

[0036] The activated carbon and nickel salt solution are mixed and dried, and then reduced with hydrogen to obtain activated carbon-supported nickel nanoparticles (denoted as Ni / C). The surface of the obtained activated carbon-supported nickel nanoparticles is then carbonized with a carbon-containing gas to obtain a supported nickel carbide-coated nickel nanocomposite material (denoted as Ni@NiC x / C).

[0037] The present invention has no special restrictions on the sources of the activated carbon and nickel salt solution, and commercial products or homemade products known to those skilled in the art can be used.

[0038] The present invention preferably adopts an equal volume impregnation method, firstly calculating the saturated adsorption solvent amount of the activated carbon, dispersing the nickel salt in a solvent that can just saturate the activated carbon with adsorption, preferably using ultrasound to make it evenly dispersed, then adding the prepared nickel salt solution dropwise to the activated carbon, and constantly stirring it to make it evenly adsorbed, and finally drying the activated carbon after adsorption.

[0039] In the present invention, the nickel salt is preferably selected from one or more of Ni(acac)2, Ni(CH3COO)2, Ni(NO3)2, NiSO4 and NiCl2; in a preferred embodiment of the present invention, the nickel salt is Ni(NO3)2·6H2O.

[0040] In the present invention, the solvent is preferably selected from one or more of ultrapure water, methanol and ethanol, and is more preferably ultrapure water.

[0041] In the present invention, the mass ratio of the activated carbon to the solvent is preferably 1:(0.8-2); the concentration of the nickel salt solution is preferably 0.4 mol / L-4 mol / L.

[0042] In the present invention, the drying temperature is preferably 60° C. to 100° C., and the drying time is preferably 0.5 h to 48 h.

[0043] In the present invention, the temperature of the hydrogen reduction is preferably 350° C. to 550° C., more preferably 500° C., and the time is preferably 1 h to 4 h, more preferably 1.5 h.

[0044] In the present invention, the carbon-containing gas is preferably selected from one or more of carbon monoxide, methane, ethylene and acetylene, and more preferably carbon monoxide, methane, ethylene or acetylene. The present invention has no particular limitation on the source of the carbon-containing gas, and commercially available products or self-made products known to those skilled in the art can be used.

[0045] The present invention has no special restrictions on the device for surface carbonization, and it can be achieved by using a tubular furnace familiar to those skilled in the art; first, the air in the tube is exhausted with nitrogen, and then a carbon-containing gas is introduced under high temperature conditions. The gas undergoes a disproportionation reaction on the surface of the nickel metal, causing carbon fragments to enter the nickel lattice, thereby generating a nickel carbide coating on the surface of the nickel nanoparticles.

[0046] In the present invention, the surface carbonization temperature is preferably 150°C to 300°C, more preferably 250°C, and the time is preferably 0.5 h to 5 h, more preferably 1 h. The present invention has no special restriction on the flow rate of the carbon-containing gas, and 30 mL / min to 100 mL / min known to those skilled in the art can be used.

[0047] In the present invention, the specific surface area of ​​Ni / C is preferably 100 m 2 / g~300 m 2 / g; the Ni@NiC x / C specific surface area is 150 m 2 / g~250 m 2 / g.

[0048] Ni-based catalysts are widely used in maleic anhydride hydrogenation reactions, but they have the following main problems: the succinic anhydride generated during the reaction will form waxy deposits on the catalyst surface similar to carbon deposits, thereby blocking the active sites of the catalyst. In addition, the active metal itself falls off during the stirring process, resulting in a low life span of traditional nickel-based catalysts used in this reaction. The present invention uses a coating strategy to first prepare Ni / C, and then simply treat Ni / C with a carbon-containing gas such as carbon monoxide. Under high temperature conditions, the carbon-containing gas reacts with Ni to form NiC on the surface of the metal particles. x Species, NiC x The shell layer can effectively prevent the adsorption and aggregation of succinic anhydride, the product of maleic anhydride hydrogenation, on the Ni surface, leading to poisoning and loss of active sites, and can also prevent metal particles from aggregating and growing during the reaction. Therefore, the catalyst is suitable for hydrogenation of maleic anhydride to produce succinic anhydride.

[0049] In the present invention, the process of catalyzing maleic anhydride to prepare succinic anhydride is preferably as follows:

[0050] The catalyst, maleic anhydride and solvent are added into a high-pressure reactor, and hydrogen is continuously introduced for hydrogenation reaction to obtain succinic anhydride.

[0051] In the present invention, the catalyst is the supported nickel carbide-coated nickel nanocomposite material described in the above technical solution, which will not be described in detail here.

[0052] The present invention has no special limitation on the sources of maleic anhydride and hydrogen, and commercial products or homemade products known to those skilled in the art can be used.

[0053] In the present invention, the solvent is preferably selected from one or more of methanol, ethanol, DMF, DMSO, toluene, n-hexane, acetone, tetrahydrofuran and 1,4-dioxane, more preferably acetone or 1,4-dioxane; the solvent here is different from the solvent in the above nickel salt solution, and the present invention will not be repeated here. The present invention has no special restrictions on the source of the solvent, and commercially available products known to those skilled in the art can be used.

[0054] In the present invention, the mass ratio of the catalyst, maleic anhydride and solvent is preferably (0.02-0.2):1:(5-50), and more preferably 0.05:1:(5-10).

[0055] In the present invention, before the hydrogenation reaction, it is preferred to further include: replacing the air in the high-pressure reactor with nitrogen.

[0056] In the present invention, the temperature of the hydrogenation reaction is preferably 80°C to 120°C, more preferably 100°C to 120°C, the hydrogen pressure is preferably 0.1 MPa to 5 MPa, more preferably 2 MPa to 4 MPa, and the time is preferably 0.5 h to 12 h, more preferably 0.5 h to 1 h.

[0057] Compared with the prior art, the present invention has the following technical effects:

[0058] (1) The present invention can obtain a high-yield succinic anhydride product by catalyzing the hydrogenation of maleic anhydride with a catalyst. Under the conditions of a temperature of 100°C, a hydrogen pressure of 3 MPa, and a catalyst to substrate mass ratio of 1:20, the conversion rate of maleic anhydride reaches 100% after 40 minutes of reaction, and the selectivity of succinic anhydride is higher than 99%. The surface shell weakens the adsorption of the product, making the structure of the catalyst more stable, and the catalyst can be repeatedly used for 8 times without deactivation. Compared with the homogeneous catalytic system, the present invention has a simple process, and the catalyst can be reused by filtering, washing and other operations after the reaction. It has high stability and can be used multiple times without performance degradation.

[0059] (2) Compared with other core-shell nickel-based catalysts, the preparation process of the present invention does not require a large amount of organic matter to coordinate with the nickel precursor, nor does it require high-temperature calcination to form. The present invention uses carbon-containing gas to disproportionately form carbon fragments and carbon dioxide on the nickel surface, and the carbon fragments enter the nickel lattice to form a shell layer. The present invention reduces the cost of catalyst preparation and is a green and environmentally friendly catalyst.

[0060] (3) The preparation process of the present invention is simple, the reaction conditions are mild, the product selectivity is high, the separation of the product and the catalyst is relatively simple, and it has universal applicability and can be produced on an industrial scale.

[0061] The present invention provides a green catalytic synthesis method of succinic anhydride, comprising the following steps: using a supported nickel carbide coated nickel nanocomposite material as a catalyst and hydrogen as a hydrogen source to catalyze maleic anhydride to prepare succinic anhydride; the supported nickel carbide coated nickel nanocomposite material is composed of an activated carbon carrier, an active metal nickel core, and a nickel carbide shell coated on the surface of the active metal nickel core; the particle size of the active metal nickel core is 5 nm to 15 nm, and the thickness of the nickel carbide shell is 0.1 nm to 10 nm. Compared with the prior art, the present invention adopts a specific nickel-based catalyst, which realizes high reaction activity of maleic anhydride hydrogenation and high selectivity of a single product succinic anhydride under milder reaction conditions, and the nickel carbide shell can protect the internal nickel nanoparticles from being poisoned, can be used multiple times, and reduce the catalyst cost. At the same time, after the reaction, the catalyst is easily separated from the hydrogenation mother liquor, can be used multiple times without deactivation, and has good stability.

[0062] In order to further illustrate the present invention, the following examples are used to explain it in detail. The raw materials used in the following examples of the present invention are all commercially available sources, among which the specific surface area of ​​the activated carbon is 800 m 2 / g~1500 m 2 / g, and the average pore size is 0.5nm~5 nm.

[0063] Example 1: Preparation of catalyst and testing of its catalytic performance

[0064] 1 g of activated carbon and 1.24 g of Ni(NO3)2·6H2O were dissolved in water, mixed evenly and dried for 8 h. 1 g of the dried solid was placed in a porcelain boat and reduced in a hydrogen atmosphere at 500 °C for 90 min, cooled with nitrogen, and a portion of the catalyst was taken out after cooling and named B (20 wt% Ni / C). The other portion was heated to 250 °C and treated with carbon monoxide for 1 h, and then cooled to obtain catalyst A (20 wt% Ni@NiC x / C).

[0065] Take 0.1 g of catalyst A and B respectively, take 2 g of maleic anhydride and 15 mL of acetone as solvent, put them into the inner lining of a 50 mL high-pressure reactor, and carry out hydrogenation reaction at a temperature of 100°C and a hydrogen pressure of 3 MPa. Before the reaction, the air in the reactor was replaced with nitrogen, and the mother liquor was analyzed by gas chromatography. The reacted catalyst was obtained by centrifugal filtration and dried for application research. The reaction conditions were 100°C and 3 MPa. The application results are shown in Tables 1-2 below.

[0066] Table 1 Performance evaluation of catalyst A

[0067]

[0068] Table 2 Performance evaluation of catalyst B

[0069]

[0070] The results show that the carbon monoxide-modified Ni-based catalyst prepared in this example has high activity in maleic anhydride hydrogenation. Under the conditions of 100°C and 3 MPa, the reaction is completed in 40 min, the maleic anhydride conversion rate is 100%, the succinic anhydride selectivity is more than 99%, and the catalyst is used 8 times without obvious deactivation.

[0071] Example 2: Comparison of different carbon-containing gases

[0072] Take 1 g of activated carbon and 1.24 g of Ni(NO3)2·6H2O, dissolve them in water, mix them evenly and dry them for 8 h; take 1 g of the dried solid and place it in a porcelain boat, reduce it in a hydrogen atmosphere at 500°C for 90 min, cool it with nitrogen, and then introduce methane, ethylene and acetylene respectively after cooling, continue to heat up to 250°C, keep it warm for 1 h, and cool it to obtain catalysts C, D and E.

[0073] Take 0.1 g of catalyst C, D, and E respectively, take 2 g of maleic anhydride and 15 mL of acetone as solvent, put them into the inner lining of a 50 mL high-pressure reactor, and carry out hydrogenation reaction at a temperature of 100°C and a hydrogen pressure of 3 MPa. Before the reaction, the air in the reactor was replaced with nitrogen, and the mother liquor was analyzed by gas chromatography. The results are shown in Table 3 below.

[0074] Table 3 Performance evaluation of catalysts C, D, and E

[0075]

[0076] Example 3: Comparison of different reaction conditions

[0077] 0.1 g of catalyst A, 2 g of maleic anhydride and 15 mL of acetone as solvent were taken respectively and placed in the inner lining of a 50 mL high-pressure reactor. A hydrogenation reaction was carried out at a given temperature and hydrogen pressure. The air in the reactor was replaced with nitrogen before the reaction. The mother liquor was analyzed by gas chromatography. The reaction conditions and reaction results are shown in Tables 4-5 below.

[0078] Table 4 Performance evaluation of catalyst A at different reaction temperatures

[0079]

[0080] Table 5 Performance evaluation of catalyst A at different reaction pressures

[0081]

[0082] Example 4: Effect of different solvents on hydrogenation reaction

[0083] Take 0.1 g of catalyst A and 2 g of maleic anhydride, use 15 mL of acetone, 1,4-dioxane and tetrahydrofuran as solvent respectively, put them into the inner lining of a 50 mL high-pressure reactor, and carry out hydrogenation reaction at a temperature of 100°C and a hydrogen pressure of 3 MPa. Before the reaction, the air in the reactor is replaced with nitrogen. After the reaction, the mother liquor is separated from the catalyst by a suction filtration device. The mother liquor is taken for gas chromatography analysis. The results are shown in Table 6 below.

[0084] Table 6 Performance evaluation of catalyst A in different solvents

[0085]

[0086] Example 5: Comparison of catalytic performance of catalysts with different particle sizes

[0087] Take 1 g of activated carbon and 1.24 g of Ni(NO3)2·6H2O and dissolve them in water. Use NaOH solution to adjust the pH value of the above precursor solution to about 8, and filter to obtain a solid. Dry the solid for 8 h. Take 1 g of the dried solid and place it in a porcelain boat. Reduce it in a hydrogen atmosphere at 500°C for 90 min, cool it with nitrogen, and then introduce acetylene after cooling. Continue to raise the temperature to 250°C, keep it warm for 1 h, and cool it to obtain catalyst H.

[0088] Take 0.1 g of catalyst A and H respectively, take 2 g of maleic anhydride and 15 mL of acetone as solvent, put them into the inner lining of a 50 mL high-pressure reactor, and carry out hydrogenation reaction at a temperature of 100°C and a hydrogen pressure of 3 MPa. Before the reaction, the air in the reactor was replaced with nitrogen, and the mother liquor was analyzed by gas chromatography. The results are shown in Table 7 below.

[0089] Table 7 Performance evaluation of catalysts A and H

[0090]

[0091] Catalyst structure and performance characterization, the results are shown in Figures 1 to 4 :

[0092] To confirm the catalyst structure, catalyst A was taken for XRD and TEM characterization test. The following conclusions can be drawn from the XRD spectrum: the diffraction peaks at 2θ=44.4°, 51.7°, and 76.2° are respectively attributed to the metal Ni (111), (200), and (220) crystal planes. Unlike Ni / C, Ni@NiC x / C Due to the carbonization of Ni surface, NiC is formed x Shell, there are diffraction peaks at 2θ=37.8° and 62.3° respectively. x From the TEM image of Ni@NiC x The particles are evenly distributed on the carbon carrier, with uniform size, and most of them are less than 10 nm. From the high-power electron microscope image, it can be seen that the Ni particles are surrounded by a coating layer with a thickness of about 1 nm, which is determined to be NiC x .

[0093] Catalysts A, B and carrier activated carbon were used for nitrogen isothermal adsorption and desorption experiments. The nitrogen adsorption and desorption isotherms were obtained by the volume method, the surface area of ​​the samples was calculated by the BET method, and the average pore size data was obtained by the Barrett-Joyner-Halenda (BJH) method. The results are shown in Table 8 below.

[0094] Table 8 Evaluation of the structural properties of catalysts A, B and carrier activated carbon

[0095]

[0096] To confirm the metal content of the catalyst, a small amount of catalyst A was taken into a beaker, concentrated sulfuric acid was added and heated until smoking, and perchloric acid and concentrated hydrochloric acid were added after cooling, and heated to dissolve. The liquid was taken for inductively coupled plasma mass spectrometry (ICP-MS) analysis, and the nickel ion content (mass fraction) in the liquid was obtained to be 19.0%.

[0097] Comparative Example 1: Comparison of precious metal catalysts

[0098] 5 wt% Pd / C (named F) and 5 wt% Pt / C (named G) catalysts were purchased from Aladdin Company; 0.2 g of catalysts C and D, 15 g of maleic anhydride, and 150 mL of tetrahydrofuran as solvent were respectively put into the inner lining of a 500 mL high-pressure reactor, and hydrogenation reaction was carried out at a temperature of 80°C and a hydrogen pressure of 1 MPa. Before the reaction, the air in the reactor was replaced with nitrogen. After the reaction, the mother liquor was separated from the catalyst by a suction filtration device, the catalyst was dried for use, and the mother liquor was analyzed by gas chromatography. The results are shown in Table 9 below.

[0099] Table 9 Performance evaluation of catalysts F and G

[0100]

[0101] Experimental results show that precious metals such as Pd and Pt not only have the ability to activate C=C double bonds, but also hydrogenate C=O bonds to produce by-products.

[0102] Comparative Example 2: Comparison with commercial Raney nickel catalyst

[0103] Take 0.1 g of commercial Raney nickel catalyst, 2 g of maleic anhydride, and 15 mL of acetone as solvent, put them into the lining of a 50 mL high-pressure reactor, and carry out hydrogenation reaction at a temperature of 100°C and a hydrogen pressure of 3 MPa. Before the reaction, the air in the reactor was replaced with nitrogen, and the mother liquor was analyzed by gas chromatography. The reacted catalyst was obtained by centrifugal filtration and dried for application research. The reaction conditions were 100°C and 3 MPa. The application results are shown in Table 10 below.

[0104] Table 10 Performance evaluation of commercial Raney nickel catalyst

[0105]

[0106] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A green catalytic synthesis method of succinic anhydride, characterized in that: The following steps are involved: The supported nickel carbide coated nickel nanocomposite material is used as a catalyst and hydrogen is used as a hydrogen source to catalyze maleic anhydride to prepare succinic anhydride; the supported nickel carbide coated nickel nanocomposite material is composed of an activated carbon carrier, an active metal nickel core and a nickel carbide shell coated on the surface of the active metal nickel core.

2. The green catalytic synthesis method of succinic anhydride according to claim 1, characterized in that: The process of catalyzing maleic anhydride to prepare succinic anhydride is specifically as follows: The catalyst, maleic anhydride and solvent are added into a high-pressure reactor, and hydrogen is continuously introduced for hydrogenation reaction to obtain succinic anhydride.

3. The green catalytic synthesis method of succinic anhydride according to claim 2, characterized in that: The mass ratio of the catalyst, maleic anhydride and solvent is (0.02-0.2):1:(5-50).

4. The green catalytic synthesis method of succinic anhydride according to claim 2, characterized in that: The temperature of the hydrogenation reaction is 80°C to 120°C, the hydrogen pressure is 0.1 MPa to 5 MPa, and the time is 0.5 h to 12 h.

5. The green catalytic synthesis method of succinic anhydride according to claim 1, characterized in that: The solvent is selected from one or more of methanol, ethanol, DMF, DMSO, toluene, n-hexane, acetone, tetrahydrofuran and 1,4-dioxane.

6. The green catalytic synthesis method of succinic anhydride according to claim 1, characterized in that: The content of active metal nickel in the supported nickel carbide-coated nickel nanocomposite material is 1 wt% to 40 wt%.

7. The green catalytic synthesis method of succinic anhydride according to claim 1, characterized in that: The specific surface area of ​​the activated carbon carrier is 800 m 2 / g~1500 m 2 / g, and the average pore size is 0.5 nm~5 nm.

8. The green catalytic synthesis method of succinic anhydride according to claim 1, characterized in that: The active metal nickel core is a face-centered cubic crystal structure.

9. The green catalytic synthesis method of succinic anhydride according to claim 1, characterized in that: The preparation method of the supported nickel carbide coated nickel nanocomposite material is specifically as follows: The activated carbon and the nickel salt solution are mixed and dried, and then reduced with hydrogen to obtain activated carbon-supported nickel nanoparticles; the surface of the obtained activated carbon-supported nickel nanoparticles is then carbonized with a carbon-containing gas to obtain a supported nickel carbide-coated nickel nanocomposite material.

10. The green catalytic synthesis method of succinic anhydride according to claim 9, characterized in that: The temperature of the hydrogen reduction is 350°C to 550°C, and the time is 1 h to 4 h; The surface carbonization temperature is 150° C. to 300° C., and the time is 0.5 h to 5 h.

Citation Information

Patent Citations

  • Catalyst for continuous production of succinic anhydride from hydrogenation of maleic anhydride and preparation method thereof

    CN101502802A

  • Catalyst for hydrogenating cis-butenedioic anhydride to prepare butanedioic anhydride and its prepn and application

    CN1453066A

  • Process for preparing succinic anhydride

    US5952514A

  • Method for generating succinic anhydride through maleic anhydride hydrogenation catalyzed by Nano-Ni

    CN102229587A

  • Method for preparing nanometer particles of nickel-carbide nickel core-shell structure

    CN103769584A